Penggunaan Fiqh Al-Maslahah Wa Al-Maqasid Dalam Fatwa-Fatwa Terpilih Negeri Perlis Dari Tahun 1998-2008 - Ismail, Faisal Husen (2011)
Maslahah is one of the sources of legislation in Islam. The acceptance of maslahah as a distinct concept either in al-fiqh in general or in maqasid al-syari‘ah in particular have made this concept be practiced by most scholars today. Even though there are pros and cons of this issue today as there are many different assumptions and views among the jurists/scholars when they referred to the usul al-fiqh at large. Hence, a misunderstanding about this concept had cause certain laws or views not in line with the syariah and even go against the syariah. The focus of this study is regarding maslahah and its connection with maqasid al-syari‘ah.